The Occurrence and Contamination Level of Ochratoxin A in Plant and Animal-Derived Food Commodities - Xianjiang Li (MDPI AG, 2021)
Ochratoxin A (OTA) is a highly toxic mycotoxin and poses great threat to human health. Due to its serious toxicity and widespread contamination, great efforts have been made to evaluate its human exposure. This review focuses on the OTA occurrence and contamination level in nine plant and animal derived food commodities: cereal, wine, coffee, beer, cocoa, dried fruit, spice, meat, and milk. The occurrence and contamination level varied greatly in food commodities and were affected by many factors, including spices, geography, climate, and storage conditions. Therefore, risk monitoring must be routinely implemented to ensure minimal OTA intake and food safety.